THE ASSESSMENT OF KARIKLINZ SYSTEM ON CHEMO-MECHANICAL REMOVAL OF CARIOUS DENTINE AND RESIDUAL BACTERIA - Galina Pancu; Sorin Andrian; Gianina Iovan; Angela Ghiorghe; Claudiu Topoliceanu; Antonia Moldovan; Andrei Georgescu; Irina Nica; Simona Stoleriu (Romanian Society of Oral Rehabilitation, 2015)
The aim of study: The aim of this study is to assess the capacity of chemo-mechanical system KariKlinz to remove carious cervical and root dental tissues and effect on cariogenic bacteria comparing with clasical mechanical method. Materials and method: The cervical and root carious lesions (n =28) (active, vital teeth) were randomly distributed to one of the next carious dentine removal methods: (Study group I) chemomechanical method Kariklinz Vladmiva (n = 14), (Study group II) classical mechanical method using conventional speed and spherical bur (n = 14). The assessment was performed using laserfluorescence method DIAGNOdent® (Kavo, Biberach, Germania) before and after preparation and microbial test (Replica Test) used for detection of Mutans Streptococcus localised on the surface of prepared cavities. Results: Both methods have similar results regarding the ability to reduce carious flora level after carious dentine removal; the percentages of residual bacteria are 2,78% for chemo-mechanical method and 2,85% for classical mechanical method. The reading of DIAGNOdent were significantly lower after cavities preparation (9,07 for chemo-mechanical method and 8,85 for classical mechanical method). Conclusions: Both excavation methods investigated in this study demonstrated similar efficiency in carious dentine removal, accordingly to results of DIAGNOdent® method and microbial test (Replica Test).